MAKING PUZZLE REDOX GAME MEDIA ON OXIDATION-REDUCTION REACTION MATERIALS (REDOX) - Syifa Sagita Fauziah; Riri Aisyah; Sari Sari (UIN Sunan Gunung Djati Bandung, 2021)
This study aims to analyze the media's validation test results and describe the appearance of the PuzzleRedox game media on oxidation-reduction (redox) reaction material. The research method used is Design-Based Research. The appearance of the media is described by making a flowchart and storyboard. Flowcharts and Storyboards contain the stages of making PuzzleRedox media, including media design, media components, andrules for using PuzzleRedox media. The media will then be tested for validity on 3 expert validators, namely media experts, material experts, and learning experts. The validator is a chemistry education lecturer at UIN Sunan Gunung Djati and a Chemistry teacher at SMA Pasundan Cikalongkulon. Based on the validity test results, the mean value of r count was 0.859, higher than the critical value of 0.30. Therefore, the game media PuzzleRedox on the oxidation-reduction (redox) reaction material is declared valid and can be used as a medium or aids in the learning process.